2019
DOI: 10.1180/mgm.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and genesis of pyrochlore apatitite from The Good Hope Carbonatite, Ontario: A potential niobium deposit

Abstract: The Good Hope carbonatite is located adjacent to the Prairie Lake alkaline rock and carbonatite complex in northwestern Ontario. The occurrence is a heterolithic breccia consisting of diverse calcite, dolomite and ferrodolomite carbonatites containing clasts of magnesio-arfvedsonite + potassium feldspar, phlogopite + potassium feldspar together with pyrochlore-bearing apatitite clasts. The apatitite occurs as angular, boudinaged and schlieren clasts up to 5 cm in maximum dimensions. In these pyrochlore occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Correlation between individual elements is present, although not very strong, suggesting different evolutionary trends for different elements. Our new and previously published data (Hogarth et al , 2000; Subbotin and Subbotina, 2000; Zurevinski and Mitchell, 2004; Walter et al , 2018; Mitchell et al , 2020; Lee et al , 2006) have revealed some common features of pyrochlore oscillatory zoning. The zoning is variable: it can be found throughout the whole crystal or in limited regions; there are also crystals without oscillatory zoning.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Correlation between individual elements is present, although not very strong, suggesting different evolutionary trends for different elements. Our new and previously published data (Hogarth et al , 2000; Subbotin and Subbotina, 2000; Zurevinski and Mitchell, 2004; Walter et al , 2018; Mitchell et al , 2020; Lee et al , 2006) have revealed some common features of pyrochlore oscillatory zoning. The zoning is variable: it can be found throughout the whole crystal or in limited regions; there are also crystals without oscillatory zoning.…”
Section: Discussionsupporting
confidence: 68%
“…Oscillatory zoning is more common than sector zoning in pyrochlore crystals (Hogarth et al , 2000; Zurevinski and Mitchell, 2004; Lee et al , 2006; Sharygin et al , 2009; Walter et al , 2018; Mitchell et al , 2020). Crystals from both Loluni and Kisete are also characterised by a distinct μm-scale oscillatory zoning (Figs 4, 5, 7, 10).…”
Section: Discussionmentioning
confidence: 99%
“…7a-c). This blue CL color is due to REE activation, mostly Eu 2+ (e.g., Marshall, 1988;Mitchell et al, 1997;Blanc et al, 2000;Kempe and Götze, 2002;Mitchell et al, 2014Mitchell et al, , 2020. A stronger activation by Sm 3+ produces violet shades in the earliest zones (cores) of the crystals (Fig.…”
Section: Apatite In Glimmerite and Carbonatitementioning
confidence: 97%
“…zH 2 O in late-stage pyrochlore (Hogarth et al, 2000;Zurevinski and Mitchell, 2004;Melgarejo et al, 2012;Chakhmouradian et al, 2015;Mitchell, 2015;Mitchell et al, 2020). This compositional variation implies an increase in Ba, Sr, REE, Pb, Si, H 2 O and vacancies resulting in deviation from ideal stoichiometry associated with the progressive alteration of magmatic pyrochlore (Lumpkin and Ewing, 1995;Lumpkin and Mariano, 1995;Williams et al, 1997;Chakhmouradian and Mitchell, 2002;Chakhmouradian et al, 2015;Mitchell, 2015).…”
Section: Introductionmentioning
confidence: 99%